PENGARUHSERVANTLEADERSHIPDAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KOMITMEN ORGANISASIONAL PADA KANTOR BADAN PENGELOLA KEUANGAN DAN ASET DAERAH OKU SELATAN - Siti Jariah; Indah Purnomowati; Novayanti Novayanti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2023)
ABSTRACT The data analysis technique used was Multiple Linear Regression. Based on the results of partial analysis, there was an influence of servant leadership on organizational commitment at the Financial and Asset Management Agency Office of the South Oku Region. with a t value of 2.778. The transformational leadership variable had an influence on organizational commitment at the Financial and Asset Management Agency Office of the South Oku Region with a t value of 2.146. Simultaneously, it was found that there was the influence of servant leadership and transformational leadership on organizational commitment at the Financial and Asset Management Agency Office of the South Oku Region. The coefficient of determination (R2) obtained was 0.820. This showed that the influence of servant leadership and transformational leadership on organizational commitment was 82.0%, while the remaining 18.0% was influenced by other variables outside of this study, namely years of service, communication, and work experience (Agustiani, 2019: 152)